DFT studies of refractive index of boron-doped diamond - Dec, Bartłomiej; Bogdanowicz, Robert (Photonics Letters of Poland, 2018)
The density functional theory is one of the optimal solutions in calculation of optical properties of materials on the quantum scale. In this paper, we have investigated refractive index of a boron-doped diamond structure with the usage of Atomistic Toolkit software from Synopsys. During this study, various methods and pseudopotentials were checked to obtain an optimal performance-accuracy method for calculation of such materials. Leading method used in calculation was used meta-GGA with Fritz-Haber Institute pseudopotential. Full Text: PDF References W. Kohn and L. J. Sham, "Self-Consistent Equations Including Exchange and Correlation Effects", Phys. Rev., vol. 140, no. 4A, pp. A1133–A1138 (1965). CrossRef J. P. Perdew, K. Burke, and M. Ernzerhof, "Generalized Gradient Approximation Made Simple", Phys. Rev. Lett., vol. 77, no. 18, pp. 3865–3868 (1996). CrossRef Y. Yan, J. Gong, and Z. Zong, "Superconductivity of p-type diamond (001) and (111) thin films: Ab initio calculations", Thin Solid Films, vol. 518, no. 17, pp. 4989–4996 (2010). CrossRef M. P. Desjarlais, "Density functional calculations of the reflectivity of shocked xenon with ionization based gap corrections", Contributions to Plasma Physics, vol. 45, no. 3–4, pp. 300–304 (2005). CrossRef L. G. Ferreira, M. Marques, and L. K. Teles, "Approximation to density functional theory for the calculation of band gaps of semiconductors", Physical Review B, vol. 78, no. 12, (2008). CrossRef J. M. Soler et al., "The SIESTA method for ab initio order- N materials simulation", Journal of Physics: Condensed Matter, vol. 14, no. 11, pp. 2745–2779 (2002). CrossRef L. Kleinman and D. M. Bylander, "Efficacious Form for Model Pseudopotentials", Phys. Rev. Lett., vol. 48, no. 20, pp. 1425–1428 (1982). CrossRef Synopsys QuantumWise, Atomistix Toolkit version 2017.12. F. Tran and P. Blaha, "Accurate Band Gaps of Semiconductors and Insulators with a Semilocal Exchange-Correlation Potential", Phys. Rev. Lett., vol. 102, no. 22, p. 226401 (2009). CrossRef D. R. Lide, Ed., CRC Handbook of Chemistry and Physics, 83rd Edition, Boca Raton, Fla.: CRC Press, 2002. N. Troullier and J. L. Martins, "Efficient pseudopotentials for plane-wave calculations", Phys. Rev. B, vol. 43, no. 3, pp. 1993–2006 (1991). CrossRef W. A. Harrison, Solid state theory. McGraw-Hill, 1970. M. Sobaszek et al., "Optical and electrical properties of ultrathin transparent nanocrystalline boron-doped diamond electrodes", Optical Materials, vol. 42, pp. 24–34 (2015). CrossRef M. Ficek et al., "Optical and electrical properties of boron doped diamond thin conductive films deposited on fused silica glass substrates", Applied Surface Science, vol. 387, pp. 846–856 (2016). CrossRef R. Maezono, A. Ma, M. D. Towler, and R. J. Needs, "Equation of State and Raman Frequency of Diamond from Quantum Monte Carlo Simulations", Phys. Rev. Lett., vol. 98, no. 2, p. 025701 (2007). CrossRef R. Bogdanowicz et al., "Opto-Electrochemical Sensing Device Based on Long-Period Grating Coated with Boron-Doped Diamond Thin Film", J. Opt. Soc. Korea, JOSK, vol. 19, no. 6, pp. 705–710, (2015). CrossRef M. Ficek et al., "Linear antenna microwave chemical vapour deposition of diamond films on long-period fiber gratings for bio-sensing applications", Opt. Mater. Express, OME, vol. 7, no. 11, pp. 3952–3962 (2017). CrossRef M. Ficek, R. Bogdanowicz, and J. Ryl, "Nanocrystalline CVD Diamond Coatings on Fused Silica Optical Fibres: Optical Properties Study", Acta Physica Polonica A, vol. 127, no. 3, pp. 868–873 (2015). CrossRef P. J. Stephens, F. J. Devlin, C. F. Chabalowski, and M. J. Frisch, "Ab Initio Calculation of Vibrational Absorption and Circular Dichroism Spectra Using Density Functional Force Fields", J. Phys. Chem., vol. 98, no. 45, pp. 11623–11627 (1994). CrossRef P. Rivero, W. Shelton, and V. Meunier, "Surface properties of hydrogenated diamond in the presence of adsorbates: A hybrid functional DFT study", Carbon, vol. 110, pp. 469–479 (2016). CrossRef